The Lived Experiences of BPO Executives’ Adoption of Artificial Intelligence (AI): An UTAUT-Based Framework - Cruz, Allan (JPAIR Multidisciplinary Research, 2026)
The rapid advancements in the use of Artificial Intelligence (AI) in the BPO industry pose opportunities and challenges to BPO executives. This study explored the lived experiences of BPO executives’ adoption of AI, using the Unified Theory of Acceptance and Use of Technology (UTAUT) as the guiding framework. The goal of the study is to gain insight into the experiences of BPO executives in their AI adoption journey in contact center operations. Phenomenological inquiry, purposive and snowball sampling techniques, and semi-structured interviews were used to gather data. Using Interpretative Phenomenological Analysis (IPA), findings revealed four (4) superordinate themes: 1) Key Challenges in AI Adoption; 2) Strategies for AI Adoption; 3) The Impact and Benefits of AI; and 4) The Evolving Role of People. Key challenges in AI adoption can be addressed using sound strategies. AI can drive performance and is generally easy to use, while social influence and facilitating conditions enable effective and continued use of AI. While AI offers numerous benefits, it also poses a threat to employees. AI can create new jobs, complement some jobs, but can also lead to job insecurity. There is a need for employees to be equipped with the skills and domain expertise necessary to adapt to the changing nature of contact center operations.